2022
DOI: 10.3389/fcvm.2022.988066
|View full text |Cite
|
Sign up to set email alerts
|

Functional comparison of phosphomimetic S15D and T160D mutants of myosin regulatory light chain exchanged in cardiac muscle preparations of HCM and WT mice

Abstract: In this study, we investigated the rescue potential of two phosphomimetic mutants of the myosin regulatory light chain (RLC, MYL2 gene), S15D, and T160D RLCs. S15D-RLC mimics phosphorylation of the established serine-15 site of the human cardiac RLC. T160D-RLC mimics the phosphorylation of threonine-160, identified by computational analysis as a high-score phosphorylation site of myosin RLC. Cardiac myosin and left ventricular papillary muscle (LVPM) fibers were isolated from a previously generated model of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(30 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…While MLC1 provides physical stability to myosin, MLC2 modulates myosin activity and facilitates the interaction of myosin with actin filaments. 19,20 Recent studies focusing on HCM-causing mutations in the genes encoding ELC (MYL3) 59 and RLC (MYL2) [60][61][62] have shown that these mutations can depopulate the SRX state, thereby suggesting that physical alterations to the light chains can change the structural state of myosin. Additionally, another layer of complexity to myosin's functionality is introduced by the phosphorylation process.…”
Section: Influence Of Myosin Light Chain Mutations and Phosphorylatio...mentioning
confidence: 99%
See 1 more Smart Citation
“…While MLC1 provides physical stability to myosin, MLC2 modulates myosin activity and facilitates the interaction of myosin with actin filaments. 19,20 Recent studies focusing on HCM-causing mutations in the genes encoding ELC (MYL3) 59 and RLC (MYL2) [60][61][62] have shown that these mutations can depopulate the SRX state, thereby suggesting that physical alterations to the light chains can change the structural state of myosin. Additionally, another layer of complexity to myosin's functionality is introduced by the phosphorylation process.…”
Section: Influence Of Myosin Light Chain Mutations and Phosphorylatio...mentioning
confidence: 99%
“…Not only does phosphorylation of MLC2 strengthen the interaction between myosin and actin 19,20 but it also facilitates the transition from the SRX to the DRX state. 21,22,61,62 Such phosphorylation events enhance the formation of force-producing crossbridges and amplify force generation. 19,63 Interestingly, an increase in MLC2 phosphorylation has been observed in HCM mouse models expressing the human A57G mutation in the MYL3 gene 59 and in human HCM hearts with the K280N mutation in the TNNT2 gene.…”
Section: Influence Of Myosin Light Chain Mutations and Phosphorylatio...mentioning
confidence: 99%
“…LVPM fibers were prepared as described earlier 18,19 . Briefly, muscle bundles were isolated from the hearts of experimental mice (wild type, Alport, and LDLR/P407) and then separated into…”
Section: Preparation Of Skinned Left Ventricular Papillary Muscle (Lv...mentioning
confidence: 99%
“…To estimate the number of myosin heads occupying the DRX versus SRX states in wild-type, Alport, and LDLR/P407 mice, Adenosine triphosphate (ATP) turnover measurements were performed using skinned LVPM, as previously described [18][19][20] . In these experiments, the fluorescent N-methylanthraniloyl (mant)-ATP was exchanged for nonfluorescent (dark) ATP in skinned LVPM fibers using the IonOptix instrument.…”
Section: Determination Of Proportion Of Myosin Heads Occupying the Dr...mentioning
confidence: 99%
See 1 more Smart Citation